Approximate solutions for strongly nonlinear oscillators by using Harmonic Balance Method - Hosen, Md. Alal; Chowdhury, Md. Sazzad Hossien (2015)
We introduce an analytical technique to solve strongly nonlinear oscillators with cubic and harmonic restoring force by using harmonic balance method (HBM). A set of nonlinear algebraic equations is appeared when HBM is imposed. In this paper, a power series solutions of these nonlinear algebraic equations gives desired results and to avoid numerical complexity. A very good agreement was found between approximate and numerical solutions, which prove that HBM is very efficient and produces high accuracy results. We found that, a second order HBM works very well and the excellent agreement of the approximate solutions with the numerical solutions. The advantage of this method is its simple procedure and applicable for many oscillatory problems arising in science and engineering.